Efficiency, productivity and environmental policy: A case study of power generation in the EU - Jurate Jaraite; Corrado Di Maria (Fondazione Eni Enrico Mattei (FEEM), 2011)
This study uses the EU public power generating sector as a case study to investigate the environmental efficiency and productivity enhancing performance of the European Union's CO2 Emissions Trading Scheme (EU ETS) in its pilot phase. Using Data Envelopment Analysis methods, we measure the environmental efficiency and the productivity growth registered in public power generation across the EU over the 1996-2007 period. In the second stage of our analysis we attempt to explain changes in productivity and efficiency over time using state-of-the-art econometric techniques. Our analysis suggests two conclusions: on the one hand carbon pricing led to an increase in environmental efficiency and to a shift outwards of the technological frontier; on the other hand, the overly generous allocation of emission permits had a negative impact on both measures. These results are shown to be robust to changes in controls and specifications.
Keywords: O38; Q48; Q58; 330; Emissions Trading; EU ETS; Environmental Efficiency; Productivity Growth; Data Envelopment Analysis; Umweltökonomik; Emissionshandel; EU-Umweltpolitik; Wirkungsanalyse; Elektrische Energietechnik; Produktivität; Technische Effizienz; Data-Envelopment-Analyse